(untitled) (Washington, D.C., 2001)
Large Mammal Restoration brings together for the first time detailed case studies of those efforts, from restoring elk in Appalachia to returning bison herds to the Great Plains to the much- publicized effort to bring back the gray wolf to Yellowstone National Park. Together these case studies offer important lessons and new ways of thinking for wildlife managers and conservation biologists involved with restoration programs. Sections examine: Approaches to determining the feasibility of a restoration program; Critical hands-on aspects of restoring large mammals; Obtaining public input into the process and gaining community support for programs; The potential of some species to return without direct human intervention, and what can be done to facilitate that natural colonization.
Keywords: Mammals; Reintroduction; United States